HUBUNGAN PENGARUH KONDISI COVID-19 TERHADAP KEPATUHAN DAN KUALITAS HIDUP PASIEN DIABETES MELITUS YANG BERKUNJUNG KE APOTEK KOTA BENGKULU - Nadia Pudiarifanti; Heti Rais Khasanah (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: The COVID-19 pandemic can affect and change various sectors of life. One of the chronic diseases that can play a role as a weight for Covid-19 is Diabetes Mellitus. The condition followed by decrease visits by diabetes mellitus patients at health facilities. The COVID-19 pandemic has had a negative psychological impact on the community in the form of anxiety for most people, health workers, the elderly, and people with chronic diseases. The purpose of study were to determine the relationship between the Covid-19 pandemic and adherence to the quality of life of diabetes mellitus patients who visited the pharmacy. The tools used in this study were the compliance questionnaire and SF 36 questionnaire to see the patient's quality of life. Method : This research is non-experimental (analytic-descriptive) with a cross-sectional design. Data collected from 70 respondents who had been diagnosed with diabetes mellitus. Result : Based on the results of this study, the compliance of diabetic patients during the pandemic was 43 (61.4%) compliant respondents, 19 (27.1%) moderately compliant respondents, and 8 (11.4%) non-compliant respondents. Compliance is related to the educational status of the respondent in a p-value of 0.00. The good category quality of life of respondents was 58 (82.9%), while in the poor category were 12 (17.1%) respondents. Quality of life is also related to education status and age of respondents in p-values of 0.05 and 0.00. Conclusion : Based on the results above, it can be concluded that have relation between the compliance with quality of life of respondents with diabetes in Pandemic Covid-19 conditions with p value 0.00.